Under-frequency load shedding for islanded distribution network - Mokhlis, Hazlie; Karimi, M.; Bakar, Ab Halim Abu (2013)
Load shedding scheme is enabler for islanding operation of a distribution network. Considering the needs of effective load shedding scheme, this paper presents a new approach of load shedding based on Under Frequency Load Shedding scheme. The scheme is based on a combination of adaptive and intelligent techniques. The disturbance magnitude is estimated by utilization of the transient behaviour of the system frequency. Dynamic simulation on an intentional islanding operation is performed on an existing Malaysia network. The test results show the scheme successfully reduces the power deficiency in islanded system.